Towards Alleviating Counterproductive Work Behaviour: A Soul Leadership View - FATIMA, DR.AFSHEEN; SHAHAB, DR. HINA; MAHMOOD, MS. SABA (The journal of contemporary issues in business and government, 2021)
This article intends to examine the role of psychological empowerment and spiritual leadership towards alleviating counter productive work behaviours (CPWB). The modern organizations do not rely on sole leadership any more, but the spiritual leadership. The present study focuses on two constructs falling under the rubric of soul leadership, i.e., employee empowerment and spiritual leadership in order to alleviate counterproductive work behaviour. In line with the environment of call centres, these two constructs based on Conservation of Resources Theory are considered sufficient to address the issue in question. Data were collected from a convenient sample of call agents working in call centres located in twin cities of Pakistan i.e., Rawalpindi and Islamabad. A total of 350 respondents were sent questionnaire where usable questionnaires were 302. Structural equation modelling technique was used to test the hypotheses. Results revealed negative and significant relationship between spiritual leadership, psychological empowerment and CPWB. Finally the implications and suggestions for future research are provided.